PENGARUH PERILAKU PROSOSIAL TERHADAP KESEJAHTERAAN PSIKOLOGIS PADA MAHASISWA UNIVERSITAS X - Fadilah Fitria Harahap, Alfalah Putri Nura’rafaa, Ridwan, Rijal Abdillah (JURNAL PENDIDIKAN DAN KEGURUAN, 2024)
This research was conducted to determine the effect of prosocial behavior on the psychological well-being of students. The research was conducted on 60 active students at University X. The measuring tool used in this research used a prosocial behavior scale which refers to aspects of prosocial behavior and psychological well-being. Data analysis uses simple linear regression analysis. Regression coefficients, significance values ​​will be evaluated to understand the extent to which prosocial behavior variables influence psychological well-being variables. The research analysis results show a p-value of >.001, which is smaller than the alpha value of 0,05, indicating a significant influence of prosocial behavior on psychological well-being. The R Square result indicates that the prosocial behavior variable influences the psychological well-being variable by 20,7%. And there is no significant difference between males and females in levels of prosocial behavior and psychological well-being.